EFEKTIVITAS METODE DISKUSI KELOMPOK DALAM MENINGKATKAN KETERAMPILAN PRESENTASI MAHASISWA DI KELAS - khodijah, Nurul (Sindoro: Cendikia Pendidikan, 2024)
Most of the presentation and discussion activities conducted by students take place in the classroom, and students only have the opportunity to present in front of the class. However, it often happens that many people still cannot utilize group discussions as a means for someone to develop speaking skills and find solutions. The objectives of this research are: a). to understand the implementation of group discussion activities, b). to test the effectiveness of using group discussions in improving students' presentation skills in class. The method used in this research is pre-experimental with the One-Group Pretest-Posttest Design model. The population in this study consists of counseling guidance students from the 2021, 2022, and 2023 batches, and the sample for this research was selected using purposive sampling. The data analysis technique used in this research employs the normality test and the Wilcoxon test. The results of this study indicate an increase in students' presentation skills by 13% with a significance value of 0.03 <0.05, a positive rank of 3.00, and a negative rank of 0.00. This is supported by the difference in average scores, with a pre-test result of 69.4 and a post-test result of 79 after the discussion. Therefore, it can be concluded that Ho is rejected and Ha is accepted, stating that "group discussions are effective in improving students' presentation skills in class." Sebagian besar kegiatan presentasi dan diskusi yang dilakukan oleh mahasiswa adalah di kelas dan mahasiswa hanya memiliki kesempatan untuk presentasi di depan kelas, namun yang sering terjadi adalah masih banyak orang yang belum bisa memanfaatkan diskusi kelompok sebagai sarana untuk seseorang mengembangkan kemampuan berbicara dan menemukan solusi. Tujuan penelitian ini adalah : a). mengetahui pelaksanaan kegiatan diskusi kelompok, b). menguji bagaimana efektivitas penggunaan diskusi kelompok dalam meningkatkan keterampilan presentasi mahasiswa di kelas. Metode yang digunakan dalam penelitian ini adalah pre eksperimental dengan menggunakan model One-Grup Pretes-Prottes Design. Populasi pada penelitian ini mahasiswa bimbingan konseling angkatan 2021, 2022, 2023 dan sampel penelitian ini menggunakan purposive sampling. Teknik analisis data penelitian ini menggunakan uji normalitas dan uji wilcoxon. Hasil penelitian ini menunjukkan adanya peningkatan keterampilan presentasi mahasiswa sebesar 13% dengan nilai signifikansi 0,03 <0,05 dengan positive rank 3,00 dan negative rank 0,00 dan didukung dengan terdapat perbedaan rata-rata, hasil prettes sebesar 69,4 dan setelah dilakukan diskusi rata-rata hasil posttesnya sebesar 79,maka dapat disimpulkan bahwa Ho ditolak dan Ha diterima yang menyatakan “diskusi kelompok efektif dalam meningkatkan keterampilan presentasi mahasiswa di kelas”